PERAN MANAJEMEN MUTU DALAM UPAYA MEWUJUDKAN ANGKUTAN RAMAH LINGKUNGAN MELALUI PROYEK KCJB - Vinka Lestari; Destia Widya Putri, Asti Artika Putri, Shafa Az Zahra Diantra (CV. Adiba Aisha Amira, 2024)
The Jakarta-Bandung Fast Train Project (KCJB) is one of the largest infrastructure initiatives in Indonesia aimed at improving connectivity and supporting economic growth. This research explores the role of quality management in realizing environmentally friendly transportation through the KCJB project. The research method used is literature study and secondary data collection, with a quantitative approach to analyze the impact of quality management on environmental sustainability and economic contribution. The research results show that the implementation of effective quality management in the KCJB project includes construction quality control, environmental management systems, as well as training and development of human resources. Construction quality control involves selecting environmentally friendly building materials, applying construction techniques that have minimal environmental impact, and closely monitoring the construction process. An ISO 14001 standard environmental management system helps manage construction waste, control emissions and reduce overall environmental impact. The KCJB project is expected to reduce the use of high-emitting private vehicles and public transportation, thereby reducing pollution levels and greenhouse gas emissions. Apart from that, this project also contributes to increasing connectivity between Jakarta and Bandung, creating jobs, and increasing investment and regional trade. Overall, this research concludes that quality management has an important role in ensuring the success of the KCJB project in creating a more environmentally friendly and sustainable transportation system, as well as encouraging new economic growth in Indonesia.